A Catholic Horace at the English Court: Paratextual Manipulations in Thomas Hawkins's Odes of Horace (1625-1638) - Belle, Marie-Alice (TTR, 2019)
This article addresses the ways in which Thomas Hawkins, a translator engaged in the cultural and literary activities of early Stuart court culture, but also in the transnational, Anglo-French Catholic networks of the time, appropriates certain Odes of Horace to assert his cultural, literary, and ideological values at the courts of Charles I and Henrietta Maria. Focusing in particular on the paratexts of the printed volume in its various editions (1625-1638), which include a translator’s preface as well as a number of commendatory poems from contemporary writers and courtiers, this article revisits Theo Hermans’s (2014a [1985]) and André Lefevere’s (2006 [1992]) seminal methods for analyzing the ‘manipulation of literary fame’ in early modern England. While confirming Hermans’s and Lefevere’s attention to issues of patronage and cultural norms, as well as the pivotal importance of paratexts as markers of such factors, I argue that the strategies of ideological and political encoding at work in the productions of English seventeenth-century court culture are best understood when approached from an “enlarged” (Tymoczko, 2005, 2007) methodological stance. This means complementing well-established analyses of literary manipulation in terms of patronage and cultural norms with specific attention to the material conditions in which translations were produced and circulated; their significance to the complex and ideologically conflicted milieu of the early Stuart court; and the social, political, and religious networks in which translators operated, well beyond the immediate circles of courtly patronage and influence.